Beyond Entertainment, What Advice and Sociocultural Values do Nzema Riddles Convey? - Yakub, Mohammed (Tautosakos darbai, 2026)
Across languages and cultures, the indigenous cultural knowledge and advisory messages entrenched in proverbs, for instance, have been extensively explored. However, the important role riddles play in imparting cultural values and behavioural principles in children and adults, especially among the Nzema, is seemingly neglected. Particularly, the absence of an investigation of Nzema riddles results in the lack of understanding of an important aspect of the Nzema oral tradition, and how the riddle genre is used to teach morality. This necessitates the present study to fill a crucial gap. Drawing on the cultural-linguistics framework, this article presents a qualitative analysis of twenty Nzema folk riddles collected from oral and written sources. The findings demonstrate that, like proverbs and folktales, significant cultural values and philosophies are also ingrained in riddles. I argue that, as in other African cultures, Nzema riddles are not merely a means of entertaining people and testing one’s cogitative capacity. Rather, they are based largely on the conceptualisations of plant and animal lives, including other entities within the ecosystem to teach sociocultural values and virtues such as patience, hard work, cooperation, tolerance, transparency and fairness, good leadership, and taking precautions. Some Nzema riddles also advise people against incest and defilement.